Pelukan bumi : air terjun berbisik, lelahku hanyut dalam pelukan alam - Sofiyah, Faiqotus (Maliki Interdisciplinary Journal, 2026)
Mental health has become a critical issue in modern life, which is full of stress. This article aims to explore the role of waterfalls as natural elements in providing therapeutic effects for mental and physical fatigue. This study uses a descriptive qualitative approach with a literature review method to analyse how sensory experiences (visual, auditory, tactile) around waterfalls can create a soothing embrace of nature. The results of the analysis show that waterfalls function as natural recovery spaces through several mechanisms, including their consistent roaring sound acting as natural white noise that reduces cortisol and promotes relaxation, their visual beauty and the presence of negative ions improving mood and vitality, and their environment, separated from urban noise, providing space for introspection and mindfulness. This article concludes that interaction with waterfalls can be an effective ecotherapy strategy for addressing psychological fatigue. Implications include the need for efforts to integrate the concept of nature therapy into public mental health policies while raising environmental conservation awareness to ensure the sustainability of this healing natural resource.